Transient Global Amnesia: An Electrophysiological Disorder Based on Cortical Spreading Depression—Transient Global Amnesia Model - Ding, Xuejiao; Peng, Dantao (Frontiers in Human Neuroscience, 2020)
Transient global amnesia (TGA) is a benign memory disorder with etiologies that have been debated for a long time. The prevalence of stressful events before a TGA attack makes it hard to overlook these precipitating factors, given that stress has the potential to organically effect the brain. Cortical spreading depression (CSD) was proposed as a possible cause decades ago. Being a regional phenomenon, CSD seems to affect every aspect of the micro-mechanism in maintaining the homeostasis of the central nervous system (CNS). Corresponding evidence regarding hemodynamic and morphological changes from TGA and CSD have been accumulated separately, but the resemblance between the two has not been systematically explored so far, which is surprising especially considering that CSD had been confirmed to cause secondary damage in the human brain. Thus, by deeply delving into the anatomic and electrophysiological properties of the CNS, the CSD-TGA model may render insights into the basic pathophysiology behind the façade of the enigmatic clinical presentation.